OPTIMALISASI KETERAMPILAN MENULIS MAHASISWA SEKOLAH TINGGI ILMU USHULUDDIN DARUSSALAM MELALUI WORKSHOP PENYUSUNAN ARTIKEL DAN STRATEGI PUBLIKASI - Fatichatus Sa'diyah; Abd Muin (LPPM IAI Dar Aswaja Rokan Hilir, 2025)
The ability to write, especially in making articles, is considered important because scientific articles are now one of the requirements for graduation or final assignments. Unfortunately, many students still struggle with the techniques and structures needed to write scientific articles, such as at the Darussalam Bangkalan College of Ushuluddin. This lack of understanding can affect their ability to complete their studies successfully. Therefore, it is imperative to provide guidance and resources to help students improve their writing skills. By improving this ability, students can better express their ideas and contribute to academic discussions. In this article, the author will discuss the results of the service related to the training of scientific article preparation for university students. This training aims to improve their writing ability. By providing the right knowledge and skills, students are expected to be able to publish scientific papers more effectively. In addition, this activity also contributes to the overall academic development of students. Therefore, this service is very important to support students' success in the academic world. In carrying out this activity, the author followed three important stages: preparation, implementation, and evaluation. First, the preparation stage includes planning and organizing everything needed for the activity. Furthermore, at the implementation stage, all plans that have been prepared are carried out systematically and regularly. After the activities are completed, the author conducts an evaluation to assess the success and effectiveness of the activities that have been carried out. Through these three stages, the author hopes to achieve the goals that have been set well. The results of this discussion state that the Workshop on articles and publication strategies was held on May 4, 2025, at the Rectorate of the Darussalam College of Ushuluddin. The workshop covered various important and interesting topics, such as article structure and the use of AI. The workshop was highly interactive with 50 students participating. The results showed that the level of understanding and enthusiasm of the students was very high.